Spatial distribution of rural poverty: last three quinquennial rounds of NSS - Jha, Raghbendra; Sharma, Anurag (2003)
The spatial distribution of poverty in India has emerged as a matter of urgent concern in recent times. This paper presents evidence on the poverty experiences of 75 NSS regions for the quinquennial rounds of 1987-88, 1993-94 and 1999-2000. The results presented here facilitate easy identification of lagging areas on which anti-poverty policy must concentrate. The economic reforms programme has been unable to make any significant dent on the spatial distribution of expenditure poverty. - Reproduced.
Keywords: Poverty